Effects of intense pulsed light treatment on tear cytokines and clinical outcomes in meibomian gland dysfunction. - Qian Li (Public Library of Science (PLoS), 2021)
Meibomian gland dysfunction (MGD) has become a prevalent ocular surface disorder. Its pathogenesis is regarded as a self-perpetuating inflammatory vicious circle. Intense Pulsed Light (IPL) treatment was recently applied to improve the meibomian gland function and reduce symptoms of MGD. However, studies investigating the change of specific inflammatory cytokines during IPL treatment remained sparse. To further figure out how IPL treatment modulates the inflammatory cytokines in tears of MGD, we therefore performed a cross-sectional study and enrolled 32 patients from March 2019 to December 2020. The patients received 3 sessions of IPL treatment (10 to 16 J/cm2) at 4-week interval. The signs and symptoms of MGD were evaluated by ocular surface disease index (OSDI), tear film breakup time (TBUT), and meibomian gland yield secretion score (MGYSS). The clinical evaluators and tear samples were analyzed at baseline and at each IPL treatment session. Concentrations of (chemokine ligand) CXCL1, (C-C motif chemokine) CCL11, (tumor necrosis factor) TNF-α, (interferon) IFN-γ, (interleukin) IL-2, IL-6 and (tissue inhibitor of metalloproteinase) TIMP-1were measured by Quantibody Human Dry Eye Disease Array1. OSDI significantly decreased after IPL treatment compared with baseline. TBUT and MGYSS increased consecutively during treatment. CXCL1, CCL11, TNF-α, IFN-γ, IL-2, IL-6 presented significantly decrease and TIMP-1 showed significantly increase from the pretreatment baseline. The changed concentrations of TNF-α, IFN-γ, IL-2, TIMP-1 correlated with TBUT, the changed values of CXCL1, TNF-α, IFN-γ, CCL11, IL-2, IL-6, TIMP-1 correlated with MGYSS, and the changed concentrations of CXCL1, IFN-γ, CCL11, IL-2, IL-6 correlated with TIMP-1. The data supported IPL treatment could significantly relieve both signs and symptoms of MGD. The therapeutic effect of IPL treatment may originate from regulation of inflammatory cytokines including CXCL1, TNF-α, IFN-γ, CCL11, IL-2, IL-6, and TIMP-1.